Віршування Лучіана Блаґи в контексті румунського експресіонізму: гетероморфні форми - Паладян, Крістінія Іванівна; Paladian, Kristinia (Східноєвропейський національний університет імені Лесі Українки, 2017)
Стаття присвячена вивченню особливостей віршованих форм Лучіана Блаґи, одного з найкращих представників румунського літературного експресіонізму. Показано, що його твори побудовані на основі гетероморфності, тобто вільного поєднання рядків різних розмірів та, іноді, різних версифікаційних систем, серед яких: вольні ямби, вольні хореї, вольні амфібрахії, які побудовані на основі типографічного членування силабо-тонічних рядків та вольні дольники, вольні тактовики і вольні акцентні вірші, створені за принципом асинтаксизму з великою кількістю перенесень (enjambment). Таким творам властивий невпорядкований характер, хвилястий графічний малюнок з різкою зміною коротких і довгих рядків, відсутність або спорадичне римування та, здебільшого, астрофічність або безсистемне поєднання версів у строфоїди. Також Л. Блаґа звернувся до гетероморфного вірша, в якому різні силабо-тонічні метри представлені врівень із різними тонічними метрами, але не створюють метричної інерції. The article is devoted to the study of the peculiarities of verse forms Lucian Blaga, one of the best representatives of Romanian literary expressionism. It has been shown that in the realm of versification the poet manifests himself as a skillful experimenter and innovative creator who tends to violate the monotony of a classical verse. His works are built on the basis of heteromorphy, that is free combination of lines with different meters and, sometimes, different systems of versification. Experimental become free meters built on the basis of syllabo-tonic versification, among which have been found: free iambus, free trochee and free amphibrach. In the basis of the structure of these meters was put the principle of typographic division of syllabo-tonic lines, which, for the most part, are not rhymed. The poet worked out numerous configurations of all meters of tonic versification – for the most part free dolniks and free taktoviks. Such works are characteristic of wavy graphic outlines with abrupt change of long and short lines as well as sporadic rhyming. The main device of creating innovations in the works is asyntactic lines with enjambments which unpredictably break the rhythmic wave of a verse. At the same time L. Blaga turned to a heteromorphic verse, in which various sillabo-tonic meters are represented on an equal footing with different tonic meters, but do not create a metric inertia.
The Versification of Lucian Blaga in the Context of Romanian Expressionism: Heteromorphic Forms
Keywords: Лучіан Блаґа; експресіонізм; віршування; вольний ямб; вольний дольник; верлібр; гетероморфний вірш; Lucian Blaga; expressionism; poetry; free iambus; free dolnik; free verse; heteromorphic verse